Comoros Poverty Assessment - World Bank (World Bank, Washington, DC, 2018)
The Poverty Assessment for Comoros aims to respond to this need and presents the first analysis using the new household survey data from 2014. The present report draws on the availability of the EESIC 2014 to provide a robust diagnostic of poverty and inequality in Comoros and to bring new evidence to better inform policies aimed at poverty alleviation and equity. The analysis is complemented with data from various sources, including the previous household survey EIM 2004 and the Demographic and Health Survey (DHS) for 2012. Through a pro-active consultation and dissemination approach, the empirical insights generated by this report are expected to turn into key findings and recommendations for local public policy debates. The first chapter of the report will provide an overview on the country’s context, assessing the macroeconomic performance and governance environment. The remaining chapters are organized as follows: the second chapter examines the incidence and structure of consumption poverty and inequality using the most recent survey, EESIC 2014. The third chapter assesses the evolution of poverty and living conditions since 2004, and investigates the extent and changes of multidimensional poverty. The fourth chapter analyzes the labor market situation and investigates the specific case of informal employment. The fifth chapter focuses on immigration and remittances, while the last chapter assesses the fiscal incidence.